2019
DOI: 10.1182/blood-2019-01-895698
|View full text |Cite
|
Sign up to set email alerts
|

Familial predisposition to TP53/complex karyotype MDS and leukemia in DNA repair-deficient xeroderma pigmentosum

Abstract: There is a Blood Commentary on this article in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…Two recent studies reported a more than a thousand-fold increased risk of hematological malignancies in independent cohorts of XP-C patients 8,9 , which demonstrated mainly myelodysplastic syndrome with secondary acute myeloid leukemia manifestation. The genetic mechanism of increased risk of internal tumors in XP patients is not well understood.…”
mentioning
confidence: 99%
“…Two recent studies reported a more than a thousand-fold increased risk of hematological malignancies in independent cohorts of XP-C patients 8,9 , which demonstrated mainly myelodysplastic syndrome with secondary acute myeloid leukemia manifestation. The genetic mechanism of increased risk of internal tumors in XP patients is not well understood.…”
mentioning
confidence: 99%
“…The c.1643_1644delTG deletion is a hotspot mutation in XPC 9,17,26–28 and a founder mutation in Northern Africa 16,27,29,30 . This variant co‐segregated with a high risk of developing haematological tumours in a few North African XP cases 28 . Interestingly, case 19P0 homozygous for this variant developed a high‐grade serous ovarian carcinoma at 27 years old.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that XPC-HR23B facilitated recognition of 8-oxoG in an OGG1-dependent BER. It is interesting to note that XP-C patients, in addition to high skin cancer rates, also have a higher incidence of internal cancer development (Giglia et al, 1998;Hollander et al, 2005;Sarasin et al, 2019). Thus, reduced kinetics of oxidatively generated DNA damage might be a major contributor to these internal cancers.…”
Section: Oxidatively Generated Base Damage Recognized By Ner Pathwaymentioning
confidence: 99%